Un pueblo cantaor - Webster, Sarah (United States : Merak'n Productions, Inc., 2001)
A short film about flamenco – its origins, development and future. The history of the Spanish Gypsies is the story of a collision between two cultures – the nomadic lifestyle and the sedentary one. It is a story of collective suffering where an entire village is persecuted and disinherited. It is also the story of a unique cultural and musical exchange in Lower Andalusia between Gypsies living there and the other rich cultures of the area, such as the Moorish and the Jewish. These influences coalesced and gave birth to flamenco. Born out of happiness and pain, cheerfulness and grief, flamenco carries with itself the collective memory of an entire village.
Soros Documentary Fund
Soros Documentary Fund
Keywords: Documentary films